The subglacial mosaic of the Laurentide Ice Sheet; a study of the interior region of southwestern Hudson Bay. (15th June 2019) - Gauthier, Michelle S.; Hodder, Tyler J.; Ross, Martin; Kelley, Samuel E.; Rochester, Andrew; McCausland, Phil
Abstract: Reconstructions of past ice-flow provide useful insights into the long-term behaviour of past ice sheets and help to understand how glaciated landscapes are shaped. Here, we present reconstruction of a 10-phase ice-flow history from southwestern Hudson Bay in northeastern Manitoba (Canada), a dynamic region situated between two major ice dispersal centres of the Laurentide Ice Sheet. We utilize a diverse geologic dataset including 1900 field-based erosional indicators, 12 streamlined-landform flowsets, esker and meltwater corridor orientations, 103 till-fabrics analyses, and 1344 till-clast lithology counts. Our reconstruction suggests that both pre-MIS 2 and MIS 2 glaciations followed similar growth patterns, where ice advanced into study area from ice centered to the east (probably in northern Quebec), followed by a switch in ice-flow direction indicating flow from the Keewatin ice centre to the northwest and north. The cause for this switch in ice-flow orientation is uncertain, but the youngest switch may relate to retreat of ice during MIS 3 that then left space for Keewatin-sourced ice to advance over the study area. While modelling experiments indicate widespread cold-based conditions in the study area during the last glacial cycle, uniformly relict landscapes are not common. Instead, the glaciated landscape is palimpsest and commonly fragmented, forming a subglacial bed mosaic of erosional and depositional assemblages that record both shifting ice-flow direction through time and shifting subglacial conditions. Each assemblage formed, or modified, during times of dynamic (warm-based) ice, and later preserved under conditions below or close to the pressure melting point (slow and sluggish, or cold-based). Highlights: Regionally integrated multi-scale observations provide insights into the evolution of core regions of ice sheets. Ten phases of ice-flow reconstructed based on four different proxies. Fragmented, complex, landscape due to subglacial bed mosaic of glacial erosion and deposition. Half of the landscape in northeastern Manitoba is a palimpsest record of older glacial events.